A new species of Chirothripoides (Thysanoptera: Tubulifera) from India and Malaysia - Tyagi, Kaomud; Mound, Laurence A.; Kumar, Vikas (Zootaxa, 2016)
Chirothripoides brahmaputrai sp.n. is described based on a holotype female from Assam State, India, and a paratype female from Peninsular Malaysia. A key to the six species of Chirothripoides is provided, and partial sequence data of mitochondrial cytochrome c oxidase (mtCOI) from the holotype of the new species is generated and submitted to Barcode of Life Database.